CRIMINAL RESPONSIBILITY FOR THE CRIMINAL ACT OF UNAUTHORIZED USE OF STATE LAND (Study in Desa Tadukan Raga Kecamatan STM Hilir) - M. Ardiansyah Bancin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Unauthorized possession of state land is a form of crime that results in state losses and disrupts orderly administration and regional spatial planning. This phenomenon is widespread in various regions, including in Tadukan Raga Village, STM Hilir District, Deli Serdang Regency. This crime raises profound legal issues related to the criminal liability of the perpetrators and the effectiveness of law enforcement by authorized officials. This problem is examined in a study entitled Criminal Liability for the Criminal Act of Land Acquisition "State Without Permission (Study in Tadukan Raga Village, STM Hilir District)". The formulation of the problem in this study is: (1) What is the form of criminal liability for perpetrators of the crime of unauthorised possession of state land in Tadukan Raga Village, STM Hilir District? (2) What are the factors causing this crime? (3) What is the role of law enforcement officials in overcoming unauthorised possession of state land in the region? This study uses a qualitative method with a field research and library research approach. This type of research is descriptive and analytical, aiming to describe and analyze in-depth legal phenomena occurring in society. Data was collected through direct observation, in-depth interviews with village officials, law enforcement officers, and local residents, legal documentation, and an ethnographic approach to understand the social dynamics underlying these crimes..